The evaluation of early stage oxidative status in streptozotocin induced diabetes in rats - Kisacam, Mehmet Ali; Kocamuftuoglu, Gonca Ozan; Ufat, Hakan; Ozan, Sema Temizer (Taylor & Francis Ltd, 2022)
Early-stage diabetes can be defined as the stages before absolute insulin deficiency in patients. In this study, the early stage oxidative effect of streptozotocin(STZ) induced diabetes mellitus was evaluated. 28 male adult Sprague-Dawley rats were divided into four groups; control group and 7th, 14th, 21st days diabetic groups. Diabetic groups received single 65 mg/kg STZ injection intraperitoneally. Rats were decapitated at 7th, 14th and 21st days, liver tissues were taken. Nitric oxide(NO), malondialdehyde(MDA) levels and catalase, arginase activities were measured. MDA and NO levels were increased (respectivelyp < .001 andp < .01), mainly 14 and 21 days after STZ administration; moreover, while liver catalase activity was progressively decreased (p < .001), oppositely arginase was increased in the same time period (p < .01). Results show that MDA and nitric oxide together with catalase and arginase switch at an early stage of diabetes and they may contribute to subsequent complications related to diabetes via increased oxidative damage.
Keywords: Diabetes; nitric oxide; malondialdehyde; arginase; catalase